StoutQuest: the journal of research at University of Wisconsin-Stout, no.4, 2010-2011 - Mell, Doug; Flom, Hannah; Couillard, Claire; Poling, Jerry, 1958- (University of Wisconsin--Stout. Provost's Office, 2011)
StoutQuest is the UW-Stout annual journal of faculty and staff research. The journal highlights the growing and diverse scholarship and applied research that happens every day among faculty, staff and students of Wisconsin's Polytechnic University.
Student research on the rise at UW-Stout -- Discovery Center busy with cross-disciplinary projects -- Scholar's research benefits from McNair program -- Work station design offers mobility, versatility -- Classes test their skills with real world projects -- Nakatani center polishes teaching, learning skills -- Professor named Biology Scholars Research Resident -- Plastics engineering students benefit from latest technology -- Class works with jail inmates to make better decisions -- UW-Stout scholarly activity in 2010 -- Professor wins award for clothing made from recycled jeans -- Fulbright scholarship takes professor to Finland -- New machines to bolster research in Fryklund Hall.
Keywords: University of Wisconsin--Stout; Research--Periodicals; University of Wisconsin--Stout. Research Services